Creating Stable Agreements in Marine Policy: Learning from the California South Coast Marine Life Protection Act Initiative. Issue 1 (18th January 2016) - McCreary, Scott; Grifman, Phyllis; Cowart, Meredith
Abstract : In this article, we examine the California South Coast Marine Life Protection Act Initiative stakeholder process, evaluate its shortcomings, and consider what could have been done differently. Our objective is to make recommendations to improve future multi‐stakeholder marine policy processes. In our view, while the South Coast stakeholder process had many positive outcomes, it failed to reach what we call here a "stable agreement." Our analysis is based on two of the authors' involvement (one as a facilitator and the other as a stakeholder representative) in the process and a post‐hoc survey of participants. We find that several ill‐advised process design and management choices significantly destabilized the negotiations, leading to an ultimately unstable agreement. We highlight four major problematic process design and management decisions, including the following: representation on the multi‐stakeholder group was imbalanced, the pre‐meeting caucuses were not paired with training in interest‐based negotiation, adequate incentives to negotiate toward a consensus agreement were not provided, and the use of straw voting at one point in the process was unclear and inconsistent. As a result of these and other process design and management flaws, many stakeholders believed that the process was biased and that their ends would be better achieved by anchoring negotiations and engaging in positional bargaining. Ultimately, this meant that near‐consensus on a single cross‐interest marine protected area proposal was not reached, the scientific guidelines put forth were not fully met, the process was not and is not viewed as fair by the stakeholders directly or indirectly involved, and the marine protected area regulations lack broad‐scale support. These pitfalls of the South Coast stakeholder process could have been avoided had the management and facilitation team consistently followed best practices in dispute resolution. We recommend that future marine planning processes learn from this example, particularly those occurring in highly complex, urban ocean environments.